QUEST FOR THE TRUTH AS REFLECTED IN EMMA DONOGHUE’S THE WONDER - Sari, Nurul Novita; Wahyono, Danu (COMMUNITY OF RESEARCH LABORATORY SURABAYA, 2025)
This study explores quest for the truth in Emma Donoghue’s The Wonder. It aims to discuss how a woman searches for the truth. Meanwhile the objectives of the study are the motivation to search the truth, and the struggles of searching the truth. It uses a qualitative method as the research design and psychological approach as a literary approach. In addition, Katsoff’s theory is used as theoretical framework. The result shows that Lib, a nurse, is assigned to investigate her patient, Anna O'Donnell who is reported to be able to survive without food for a couple of months. It challenges her because she sees the strong beliefs of the environment. She realizes that questing the truth is not just about finding the proofs. It is a belief system that demands her excessive sacrifice. She has a strong motivation to fight to find the truth. She gets profession-responsibility to investigate her patient. She struggles to manage her patient and has a commitment to bring Anna O'Donnell to a new life. Her struggles to quest the truth are not only internal, but also external. She faces strong resistance from Anna’s family and the fanatical village community. She conducts a great effort to quest the truth of her patient’s case. She is able to save Anna's life by reviving Anna's soul as a new identity.